SCIENCE-DRIVEN EDUCATION AS A PRECONDITION FOR THE FORMATION OF THE COMPETITIVE UKRAINIAN ECONOMY - S. Dovgyi; O. Topuzov; M. Halchenko; T. Matusevych; F. Revin (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. Today, the growing needs of the labor market in qualified personnel and the strategic objectives of Ukraine to form a competitive economy require radical changes in the education sector by introducing science-intensive education and research-oriented training to develop Competencies 4.0. The comparative analysis confirmed the inconsistency of the structure of training of specialists of Ukraine not only with the similar structure in developed countries but even with the structure of countries with the appropriate level of economic development. To solve mentioned problem on the basis of the study, the article presents: the structure of systemic interaction of the activities of higher education institutions and the structure of their funding with the involvement of institutional and extra-budgetary sources; proposed normative-legal, organizational, financial measures aimed at increasing the quality of education, which would correspond to the level of the world’s leading countries. Activities include specific recommendations, such as encouraging students to do research using a sub-project approach with separate terms of reference and budget; non-financial involvement of students in the research projects of leading scientists as a tool to stimulate the acquisition of new skills and knowledge, the rating approach — «the best student — the best researcher», etc. Using the methods of mathematical formalization, a forecast of the deterioration of the quality indicator of mathematical and natural education was formed, which became the justification for the urgency of educational reforms; the existence of correlation of nominal GDP per capita from the indicator of the quality of mathematical and natural education is proved and the values of time intervals necessary for the manifestation of this dependence are established. These research results provide an opportunity for both scientists and management practitioners to use them in their work.